Foreign market entry in transition economies: Entry timing and mode choice - Kristian Jakobsen (Copenhagen Business School (CBS), 2008)
This dissertation consists of an introduction followed by four papers on issues related to the choice of entry timing and entry mode in transition economies. Below is a list of the papers that is included in the dissertation with information about their current publication status and coauthorships. * Jakobsen, K. 2007. First mover advantages in Central and Eastern Europe: A comparative analysis of performance measures, Journal of East-West Business, 13(1), 35-61. * Jakobsen, K. 2008. Competition for Markets in the Brewing Industry in Central and Eastern Europe. In J. Larimo (Ed.) Perspectives on Internationalization and International Management, Vassan Yliopiston Julkaisuja, p. 299-316. ISBN 978-952-476-228-1 * Jakobsen, K., & Meyer, K. E. 2008. Partial Acquisition: The overlooked entry mode. In J. H. Dunning and P. Gugler (eds.) Progress in International Business Research 2, Elsevier Science, p. 203-226. ISBN 978-0-7623-1475-1. * Jakobsen, K., & Meyer, K. E. 2007. Negotiating entry modes: Partial acquisitions in transition economies. Revise and resubmit at International Business Review
hdl:10398/7681
Keywords: 650